COMPARISON TENSILE STRENGTH OF NATURAL AND SYNTHETIC ABSORBABLE SUTURES - NINDHIA, TJOKORDA GDE TIRTA; ASTAWA I., PUTU; NINDHIA, TJOKORDA SARI; SURATA I., WAYAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the investigation is to evaluate and to compare the tensile strength of commercial natural and synthetic absorbable suture materials currently used in surgery. The natural absorbable sutures of chromic catgut are prepared for this purpose as well as commercial synthetic absorbable sutures made from polyglycolide. Methods: The analysis has been carried out following the standard test method for tensile strength and Young’s modulus of fiber ASTM C1557-03. Measuring the diameter of each suture has been carried out with an optical microscope to determine the accuracy of manufacturers’ data. Tensile testing has been performed to evaluate the tensile strength of each type of sutures. The modulus elasticity and strain (ϵ) obtained are also presented. Results: The results show that sutures made from braided synthetic material of polyglycolide (violet coated) present a tensile strength remarkably superior (1070.292 MPa) to that of natural absorbable sutures of chromic catgut (392.276 MPa). Using optical macro microscope analysis, monofilament sutures present less surface irregularities than multifilament polyglycolide sutures. Chromic catgut monofilament sutures present less surface irregularities than multifilament polyglycolide. Conclusion: Tensile test of absorbable sutures was conducted in this research. Two types of absorbable sutures were investigated and compared. It is found that sutures made from braided synthetic material of polyglycolide (violet coated) having much better tensile strength comparing with sutures made from natural material (chromic catgut monofilament).